2011
DOI: 10.1093/pcp/pcr145
|View full text |Cite
|
Sign up to set email alerts
|

TAT-Mediated Aequorin Transduction: An Alternative Approach for Effective Calcium Measurements in Plant Cells

Abstract: Cell-penetrating peptides are short cationic peptides with the property of translocating across the plasma membrane and transferring macromolecules otherwise unable to permeate cell membranes. We investigated the potential ability of the protein transduction domain derived from amino acids 47-57 of the human immunodeficiency virus type 1 (HIV-1) TAT (transactivator of transcription) protein to be used as a nanocarrier for the delivery of aequorin, a Ca(2+)-sensitive photoprotein widely used as a reliable Ca(2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Baumgärtner et al [35] found that the cellular internalization of the serpin protein C inhibitor (PCI) is supported by plasma membrane PE, which enables its rapid targeting to the nucleus both in vitro and in vivo. Therefore, PCI was considered as an excellent candidate for the nuclear supply of cargo.…”
Section: Molecular Modeling Approachesmentioning
confidence: 99%
See 4 more Smart Citations
“…Baumgärtner et al [35] found that the cellular internalization of the serpin protein C inhibitor (PCI) is supported by plasma membrane PE, which enables its rapid targeting to the nucleus both in vitro and in vivo. Therefore, PCI was considered as an excellent candidate for the nuclear supply of cargo.…”
Section: Molecular Modeling Approachesmentioning
confidence: 99%
“…CPP-endosomal escape is one major challenge in CPP cargo delivery and several studies have focused on investigating the mechanisms of endosomal escape of CPPs [ 35 ]. In an elegant experiment, the biological endosome can be modeled using the bacteriorhodopsin (BR)-reconstituted LUV system (BR-LUV).…”
Section: Model Membrane Interactions Of Cppsmentioning
confidence: 99%
See 3 more Smart Citations